2022
DOI: 10.3390/plants11070960
|View full text |Cite
|
Sign up to set email alerts
|

Spicy and Aromatic Plants for Meat and Meat Analogues Applications

Abstract: Aromatic and spicy plants are an important factor that contributes not only to improving the taste of meat, meat products, and meat analogues, but also to increasing the nutritional value of the products to which they are added. The aim of this paper is to present the latest information on the bioactive antioxidant and antimicrobial properties of the most commonly used herbs and spices (parsley, dill, basil, oregano, sage, coriander, rosemary, marjoram, tarragon, bay, thyme, and mint) used in the meat and meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 157 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…In support of the abovementioned outcomes, the results of in silico screening also highlighted the importance of rosmarinic acid, which presented the highest binding affinity for AR among the selected compounds [66]. Therefore, the herbs M. spicata, O. vulgare and T. capitatus, which contain high amounts of rosmarinic acid and belong to the Lamiaceae family [67][68][69], show promise as herbal preparations with considerable antihyperglycemic activity. Special focus should be paid to T. capitatus because its putative action against hyperglycemia-related conditions may be attributed to the synergistic effect of rosmarinic acid and naringenin, which also presented putative binding affinity against AR [70].…”
Section: Phytochemical Phenolic Profile Of the Examined Infusion By L...mentioning
confidence: 53%
“…In support of the abovementioned outcomes, the results of in silico screening also highlighted the importance of rosmarinic acid, which presented the highest binding affinity for AR among the selected compounds [66]. Therefore, the herbs M. spicata, O. vulgare and T. capitatus, which contain high amounts of rosmarinic acid and belong to the Lamiaceae family [67][68][69], show promise as herbal preparations with considerable antihyperglycemic activity. Special focus should be paid to T. capitatus because its putative action against hyperglycemia-related conditions may be attributed to the synergistic effect of rosmarinic acid and naringenin, which also presented putative binding affinity against AR [70].…”
Section: Phytochemical Phenolic Profile Of the Examined Infusion By L...mentioning
confidence: 53%
“… 21 Some polyphenol compounds present in O. basilicum are apigenin-7-glucuronide, dihydrokaempferol-3-glucoside, and aesculetin. 22 , 23 The previous study reported that apigenin-7-glucuronide has antimicrobial activity against Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris , and Pseudomonas aeruginosa . 24 Dihydrokaempferol-3-glucoside was reported to have antioxidant activity of 1.0 mmol Trolox/mmol by Trolox equivalent assay.…”
Section: Discussionmentioning
confidence: 99%
“…Dried onions, dried garlic, curry powder, black pepper, garlic, chili, paprika and ginger are among the most widely used spice mixtures [120]. According to Vlaic et al [178], the most widely used aromatic plants in plant-based meat production are parsley, dill, basil, oregano, sage, coriander, rosemary, marjoram, tarragon, bay, thyme and mint. The mentioned herbs contain bioactive molecules that can have a beneficial effect on human health.…”
Section: Spicesmentioning
confidence: 99%